Investasi di Pasar Modal : Mengelola Risiko dan Meraih Keuntungan - Dini Selasi; Amelia Nur’aeni; Vika Mariska Septiana (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The capital market plays a significant role in modern economies by providing a platform for individuals and companies to raise funds and invest. This study explores the dynamics of capital market investments, focusing on managing risks and maximizing returns. The objective is to understand the types of risks involved in capital market investments and identify strategies for effective risk management. The research uses qualitative methods, reviewing literature and analyzing case studies of successful capital market investments. The findings suggest that diversification, hedging, and portfolio management are key strategies in minimizing risks, while long-term investments and active trading offer significant profit potential. The study concludes that a deep understanding of market conditions, coupled with risk management techniques, is essential for investors to achieve sustainable profits. The implications of this research highlight the importance of financial education in making informed investment decisions and the role of the capital market in economic growth.